Utilization of demolished tile material and cement to stabilize marine clay - Hillary, Ermyza (2022)
The presence of marine clay soil in the fundamental establishment has been liable for the disappointment in a few geotechnical designs. Substance techniques for soil improvement are the typical practices to work on the strength of soils. Nonetheless, distributions on the key microstructural conduct of traditional materials stirred in with waste material added substance to treated marine clay soils and their effect on the designing conduct are restricted. Malaysia is rich with huge stores of rock stone, which is a kind of Demolished Tile Material (DTM), that leads to contamination because of the procedures and cycles utilized during manufacturing and the idea of the high alkalinity of this waste. However, this research aimed at determining the stabilisation mechanism and performance of marine clay soil treated by traditional stabiliser and waste material additive, specifically cement and DTM. The utilization of DTM helps to reduce the negative impacts on the environment through recycling. As for the macrostructural tests, the unconfined compressive test (UCS) and oedometer consolidation tests were implemented to evaluate the engineering properties of the treated soil. Microstructural studies from various spectroscopic and microscopic techniques, such as X-ray Diffractometry (XRD), Energy-Dispersive X-ray Spectrometry (EDX) and Scanning Electron Microscopy (SEM) had been conducted to explain the adjustment system. The research test results show the variety of cement and DTM rates at day 0 until 60 days of the curing period. The laboratory tests showed that the addition of 16% (as the optimum amount) of DTM additive increased the strength along the curing period. The compressibility of treated soils decreased with the increase in the curing period. The microstructural study revealed that the stabilisation process modified the porous network of marine clay soil. The consequences of the microstructural tests demonstrated the development of another mineral item in the blends, which was recognized as Calcium Aluminium Silicate Hydrate (CASH) for treated marine clay. In XRD test, a slight decrease in the intensity of kaolinite and montmorillonite peak for treated soils with C10% mixed with various percentages of DTM was identified. While, in EDX test the consumption of Ca, Al and Si was confirmed with the increase in the DTM in treated marine clay soils. In short, the chosen materials for marine clay treatment had effectively improved the strength of marine clay at an early period as expected and the use of the chosen waste material additive was considered as low carbon and harmless to the ecosystem for the geotechnical projects.